Drug Compounding, Drug Safety, and the First Amendment - Dresser, Rebecca (The Hastings Center report, 2013)
In September 2012, news broke of a developing drug disaster in the United States. Health authorities had linked a fungal meningitis outbreak to a contaminated steroid made by a company called the New England Compounding Center. The contaminated steroid was a compounded drug that had not been approved by the Food and Drug Administration, differing from three others that had been approved in that it lacked preservatives present in those agents. Factory inspections revealed unsanitary conditions at NECC's drug production facility. By the time the source of the outbreak was identified, an estimated fourteen thousand people had been injected with the drug. As of December 2012, thirty-nine had died of meningitis, and hundreds more had been diagnosed with meningitis and other drug-related conditions. Many factors contributed to this disaster. One was a 2002 Supreme Court decision holding that a law prohibiting providers of compounded drugs from promoting their products through advertising and other means impermissibly restricted commercial speech.